ANALYSIS OF CHARISMATIC AND VISIONARY LEADERSHIP MODELS - Maulida, Ratna Siti; Maharani Windu Utami; Encep Syarifudin; Rifyal Ahmad Lugowi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Leadership is an important element in determining the direction and success of an organization. Two leadership models that are widely discussed in the context of modern organizations are charismatic and visionary leadership. This study aims to analyze the characteristics, advantages, shortcomings, and influence of the two leadership models on organizational performance and employee motivation. Charismatic leadership focuses on the leader's personal appeal, which is able to inspire followers through a strong personality and communication. Meanwhile, visionary leadership emphasizes the importance of a clear long-term vision and the ability to steer the organization toward strategic goals. This analysis uses a qualitative approach through literature review from various academic sources and case studies. The results of the analysis show that both models have a positive impact on the organization, especially in improving morale, commitment, and adaptation to change, although both also have potential risks if not balanced with a sound management system. These findings are expected to contribute to the development of effective leadership strategies in the context of dynamic and competitive organizations.